Pengaruh Jumlah Penjualan Pizza Terhadap Pendapatan di Usaha Rumahan Fauziah Gampong Ujung Kalak Kabupaten Aceh Barat - Putri Natasya (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research was conducted to determine the effect of the number of pizza sales on income in the Fauziah Home-based Business, Gampong Ujung Kalak, Johan Pahlawan District, West Aceh Regency. This research is located in Gampong Ujung Kalak, Johan Pahlawan District, West Aceh Regency. The population in this study were the owner and 2 employees at Fauziah's Home-Based Pizza Business with the overall sampling being carried out due to the small population. Data collection in this study was carried out using two techniques, namely library research from guidebooks related to research and field research by direct observation or observation of the object to be studied, interviews with the owner of Fauziah's home-based pizza business and by filling out a questionnaire from the business owner. Based on the research analysis, it can be concluded that the total total costs incurred amounted to Rp. 12,136,375 per month, the total amount of revenue is Rp. 15,325,000, per month, so the total income is Rp. 3,188,625 per month. This explains that the number of pizza sales affects the amount of income in Fauziah's Home Business, Gampong Ujung Kalak, Johan Pahlawan District, West Aceh Regency. The advice that can be given from the results of this study is that it is hoped that the government will be able to provide business capital assistance and counseling to the Fauziah Home-Based Pizza Business in Gampong Ujung Kalak, Johan Pahlawan District, West Aceh Regency so that they can run their business properly and get profits in accordance with the expectations of business owners.